The Effectiveness of Cultural Literacy and Citizenship through Staging Creativity against Global Diversity Characters of Elementary School Students - Lidyawati Sri Lestari; Zaka Hadikusuma Ramadan (Universitas Pendidikan Ganesha, 2023)
This research is motivated by the decline in students' global diversity character as well as the lack of optimization of its application in elementary schools. This study aims to analyze the effectiveness of cultural and civic literacy through creativity performances in improving students' global diversity character in elementary schools. The method used in this research is a quasi-experiment method with a non-equivalent control group design using an experimental class and a control class. Data analysis techniques in this study used descriptive analysis and prerequisite tests, namely the normality test and homogeneity test. Furthermore, hypothesis testing was carried out with the Independent Sample T-Test test and N-Gain data analysis. The results of this study show that applying cultural and civic literacy through creative performances effectively improves the character of global diversity of fifth grade elementary school students. There is significant difference in effectiveness between the experimental group and the control group on the global diversity character of grade V elementary school students. The treatment in the experimental group by implementing cultural literacy and citizenship through staging creativity is effective in increasing the character of global diversity in fifth grade elementary school students.